Pembuatan Gas Metana Dari Gas Karbon Dioksida (CO2) Menggunakan Katalis Ni/Al2O3 Dengan Promotor Logam Fe - Tiara Manda Putri; Robert Junaidi; Anerasari Meidinariasty (Fakultas Teknik, 2023)
Carbon dioxide (CO2) is one of the most critical greenhouse effect causes. One method that can reduce the problem of global warming is by converting CO2 and utilizing it into a CO2 hydrogenation reaction into methane. This research aims to obtain methane gas from CO2 gas using a Fixed Bed Reactor for the CO2 methanation process. This research uses Ni/Al2O3 catalyst as support and Fe metal as a promoter with in situ method by varying the amount of Fe metal promoter up to 1gr - 5gr and time variation of 30 minutes, 45 minutes and 60 minutes. The highest methane gas yield was obtained in sample 15 with more Fe metal promoter 5 gr (variation 1-5 gr) for 60 minutes (variation 30, 45, and 60 minutes), which amounted to 12.54%. The amount of Fe metal promoter and the length of time used is directly proportional to the methane gas (CH4) produced. This is because the addition of Fe as a promoter can increase catalyst activity and catalyst stability, so that the catalyst can work well in converting CO2 into methane thermal gas.Keywords: Carbon Dioxide, CO2 Methanation, Catalyst Ni/Al2O3, Promoter Fe, Methane (CH4).